Impact of geopolitical risk, GDP, inflation, interest rate, and trade openness on foreign direct investment: Evidence from five Southeast Asian countries - Md. Shaddam Hossain; Liton Chandra Voumik; Tahsin Tabassum Ahmed; Mehnaz Binta Alam; Zabin Tasmim (Regional Sustainability)
Historically, geopolitical risk (GPR) has posed significant challenges to international economic, social, and political frameworks. This study investigated how internal GPR in the selected five Southeast Asian countries (Indonesia, South Korea, Malaysia, the Philippines, and Thailand) influences foreign direct investment (FDI) during 1996–2019. The stationarity of the data was assessed using the Augmented Dickey-Fuller (ADF) unit root test, which shows that the data became stationary after the first difference. The Kao, Pedroni, and Westerlund cointegration tests were employed to examine long-term cointegration among the selected variables (FDI, GPR index (GPRI), gross domestic product (GDP), inflation, interest rate, and trade openness (TOP)). The results indicated that these variables have a long-term cointegration. Consequently, regression analysis using the Pooled Ordinary Least Squares (OLS) regression, fixed effect, random effect, Arellano-Bond dynamic panel-data estimation, and system generalized moment method (GMM) revealed that GPRI and TOP negatively impacted FDI in the selected five Southeast Asian countries. At the same time, GDP, inflation, and interest rate positively influenced FDI in these countries. Because FDI is crucial to shaping a country’s macroeconomic structure, this study recommends that governments and central banks of the selected five Southeast Asian countries should implement policies and strategies to encourage foreign investments.